Sistem Pengering Pakaian Otomatis Berbasis Microcontroller - Muhammad Shofiyullah; Syahri Muharom (Prosiding Seminar Nasional Teknik Elektro, Sistem Informasi, dan Teknik Informatika (SNESTIK), 2023)
Currently, most of the drying is still done in the traditional way of drying clothes in the hot sun, this method is very dependent on sunlight. The problem often occurs, when the rainy season comes, clothes take a long time to dry due to lack of sunlight, so clothes are easily moldy. Based on these problems, the researchers created an automatic clothes drying system using an artificial heater. The system is equipped with microcontroller as the main system, a hair dryer and two fans. This system works by heating ambient air, then circulating the air through a mechanical interior to help dry the air. Based on tests carried out on three fabrics, denim, wool and satin, the system can dry clothes in an average of 30 minutes. Based on this research, it is hoped that it can help dry clothes when the weather is less sunny or during the rainy season.